Exploring the drivers of business model innovation: Insights from a single-case study in agribusiness - Xavier, R.; Pereira, R. (Proceedings of the 18th European Conference on Innovation and Entrepreneurship, part 2, 2023)
Business model innovation has become a crucial factor for firms to remain competitive and achieve sustained success in today's rapidly changing business environment. The concept of business model innovation involves fundamentally changing the way a firm creates, delivers, and captures value, with the aim of creating value for the customer and capturing value for the company. However, despite its importance, the factors that drive firms to innovate their business models are not well understood and often assumed to be driven solely by profit. To address this gap in understanding, this research aims to examine the drivers of business model innovation in firms. Through a review of existing literature and a single case study, the study will explore the motivations and pressures that lead firms to seek new business models, as well as the internal and external factors that influence their ability to successfully implement these innovations. The case study will provide a deeper insight into the real-world complexities of business model innovation and will shed light on the practical considerations and challenges that firm faced in this process. The findings of this study will contribute to a deeper understanding of the drivers of business model innovation. By exploring the strategic, organizational, and external factors that influence the decision to innovate, this study will provide a more nuanced view of the complex process of business model innovation. In conclusion, this research will provide valuable insights for both practitioners and scholars on the factors that drive firms to innovate their business models and the factors that may influence their ability to successfully implement these innovations. By exploring the complexities of business model innovation through a single case study, this research will contribute to the existing literature and provide a practical example of a firm looking to stay ahead of the curve and maintain a competitive advantage.